(untitled) (Medico Legal Update, 2020)
Double J ureteral stents have been used to relieve or improve drainage in cases of ureteric obstruction from any causes (intrinsic or extrinsic). These forgotten or retained ureteral stents could lead to many complications. The objective of the paper is to assess the methods that used for treatment of neglected double Jamong displaced persons. Across section study was done, 28 patients with neglected double J stent were chosen from urology departments in Al-Ramadi & Al-Fallujah teaching hospitals. Result: Out of total (28) , 20 (71.4%) were males while females were 8 (28.6%) of the sample. The indication of insertion varied between 13 (46.4% ) patients after Ureterorenoscopy procedure for ureteric stones (10 males & 3 females ) and five (17.9% ) patients due to traumatic causes , four (14.3%) patients due to pyelolithotomy , three (10.7%) patients PNL for removal of renal stone. The complications rare which ranged from fever postoperatively in nine patients (32.1%), two patients (7.1%) suffered from ureteric injury thatmandate double J insertion , three patients (10.7%) required more than two sessions to clear the ureter & remove of retained double J.